The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1063/1.1462579
|View full text |Cite
|
Sign up to set email alerts
|

Collision-induced dissociation and photodetachment of singly and doubly charged anionic polynuclear transition metal carbonyl clusters: Ru3Co(CO)13−, Ru6C(CO)162−, and Ru6(CO)182−

Abstract: Three polynuclear transition metal carbonyl cluster anions, Ru3Co(CO)13−, Ru6C(CO)162−, and Ru6(CO)182− have been studied using energy-dependent electrospray ionization mass spectrometry (EDESI–MS) and photodetachment photoelectron spectroscopy (PES). EDESI–MS maps show a simple collision-induced dissociation (CID) process for Ru3Co(CO)n− by stripping CO down to the metal core. For the doubly charged species, two competing CID channels were observed, viz. loss of neutral CO and loss of CO+e−. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…EDESI-MS is a method of collecting and visualizing collections of data from collision-induced dissociation (CID) experiments. [14][15][16][17] Similar CID studies have been performed on metal-centered water clusters to probe solvation, fragmentation pathways, and solvent coordination chemistry. [18,19] Herein, we used EDESI-MS to observe the loss of water molecules from nanodroplets of water that contained different methylated guanidinium ions.…”
Section: Abstract: Highly Solvated Methylated Guanidinium Ions ([Me Nmentioning
confidence: 99%
“…EDESI-MS is a method of collecting and visualizing collections of data from collision-induced dissociation (CID) experiments. [14][15][16][17] Similar CID studies have been performed on metal-centered water clusters to probe solvation, fragmentation pathways, and solvent coordination chemistry. [18,19] Herein, we used EDESI-MS to observe the loss of water molecules from nanodroplets of water that contained different methylated guanidinium ions.…”
Section: Abstract: Highly Solvated Methylated Guanidinium Ions ([Me Nmentioning
confidence: 99%
“…Again, the 18-electron rule is useful to describe stable stoichiometries. Unsaturated metal carbonyls have also been produced and isolated in rare gas matrices [6,22] or in the gas phase via photoelectron spectroscopy of mass-selected anions [23][24][25][26]. The frequency of the CO stretch in all of these systems shifts systematically depending on the electronic structure and bonding, and these effects have been studied extensively with theory [6,22,[27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding cluster k values of the fragment should be on the increase. Very interesting extensive work on the metal carbonyls that involves stripping off the CO ligands has been done by several research groups (Butcher, et al, 2002(Butcher, et al, , 2003Crawford, et al, 2006;Critchley, et al, 1999;Dyson, et al, 2001;Henderson, et al, 1998Henderson, et al, , 2009 Table 7). Although the series and the skeletal numbers predict that each of the Re skeletal atoms except one should have a hydrogen atom, the structural determination indicates all the hydrogen atoms are bridging (Miessler, et al, 2014) as observed in borane clusters.…”
Section: Limits Of the Carbonyl Cluster Seriesmentioning
confidence: 99%
“…These opposing processes are reflected in Tables 7 and 8. The removal of CO ligands from transition metal carbonyl clusters has been an intense field of research (Critchley, et al, 1999, Douglas, et al, 2001, Butcher, et al, 2002, 2003, Crawford, et al, 2006, Henderson, et al, 2009). The silicon clusters Si n (n=4-10) were theoretically studied (Slee, et al, 1989) (Hughes, et al, 2000).…”
Section: Capping and De-capping Seriesmentioning
confidence: 99%